Nas trilhas de Paris, David Harvey e a capital da modernidade - Tadeu Alencar Arrais (Confins)
Paris, capital of modernity can be read as a kind of synthesis of the work of David Harvey as it brings together two remarkable features of his intellectual trajectory. The first relates to the interest in urban studies, establishing a tradition dating back to the book Social justice and the city (Harvey, 1980). The second concern is based on explaining the relationship between the capital and the production of space. The capital, in Harvey, is not an abstract notion. It moves, and every time, transforms the forms and the contents of the space. When he qualifies Paris as “the capital of modernity”, the geographer makes the city an icon of that historical period, resulting in the development of a comprehensive mapping of its own conflicts about the production of urban space. From the tracks left by the author, we investigate the constitution of the urban area of ​​the French capital so that, shortly after, we may analyze the way to see the city of Honoré de Balzac (1799-1850) and how to intervene in the city of Eugène Haussmann (1809 -1891). Then, we discuss the relevance of the city approach mode proposed by David Harvey from what we qualify as landscape political memory.